2016
DOI: 10.1038/srep34498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methyl salicylate (MeSA), an elicitor on growth, physiology and pathology of resistant and susceptible rice varieties

Abstract: Methyl salicylate (MeSA) is a volatile organic compound synthesized from salicylic acid (SA) a plant hormone that helps to fight against plant disease. Seed treatment with MeSA, is an encouraging method to the seed industry to produce more growth and yield. The aim of our study is to find out the growth, development and disease tolerance of rice seed treated with different concentrations of MeSA. Also the seed treatments were studied to determine whether they directly influenced seedling emergence and growth i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 53 publications
(67 reference statements)
1
32
0
Order By: Relevance
“…Seaweeds are being sought out as potential enhancers of crop growth and yield and are replacing chemical fertilizers owing to higher efficiencies, broader action range, eco-friendly nature, and cost-effective feature. Seaweeds, reported with outstanding plant growth promoting potentials, increased plant height, root as well as shoot lengths, consequently, are designated as plant growth biostimulants, as reviewed by Khan et al [7] and Craigie [33] As a crucial and initial plant growth activity, the evaluation of a seed's germination and associated parameters can help in determining the rate of a crop success, in terms of yield and economy [34]. As contemplation, the current investigation was performed to determine the plant growth stimulant activities of green seaweed U. flexuosa (Chlorophyceae).…”
Section: Discussionmentioning
confidence: 99%
“…Seaweeds are being sought out as potential enhancers of crop growth and yield and are replacing chemical fertilizers owing to higher efficiencies, broader action range, eco-friendly nature, and cost-effective feature. Seaweeds, reported with outstanding plant growth promoting potentials, increased plant height, root as well as shoot lengths, consequently, are designated as plant growth biostimulants, as reviewed by Khan et al [7] and Craigie [33] As a crucial and initial plant growth activity, the evaluation of a seed's germination and associated parameters can help in determining the rate of a crop success, in terms of yield and economy [34]. As contemplation, the current investigation was performed to determine the plant growth stimulant activities of green seaweed U. flexuosa (Chlorophyceae).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that methyl salicylate is an efficient elicitor for rice both in plant treatment, inducing defense against the leaf folder, Cnaphalocrocis medinalis Guenée, 1854 (Lepidoptera: Crambidae), and in seed treatment, to protect against bacterial blight disease ( Xanhomonas oryzae pv. oryzae ( Xoo ) …”
Section: Discussionmentioning
confidence: 99%
“…However, chemical insecticide application against the rice leaf‐folder is not advisable because of pest resistance and resurgence. Furthermore, rice leaf‐folders have a vast array of natural enemies that help maintain their populations below economic loss levels . The rice leaf‐folder has grown in economic importance with the introduction of high‐yielding rice strains and constant cultivation of the crop…”
Section: Introductionmentioning
confidence: 99%